Spiritually-Oriented Cognitive-Behavioral Family Therapy - Tuğba Turgut; Füsun Ekşi (Spiritual Psychology and Counseling)
A great many factors influence human life. Among these are individuals’ religious and spiritual orientations, whose importance cannot be understated as they not only affect how individuals perceive and interpret themselves, events in their everyday lives, and the greater world but also shape their thoughts, feelings, and behaviors. Consequently, religious and spiritual orientations constitute an integral part of clients’ lives and are an important element that needs to be thoroughly investigated. In addition to having been integrated into individual psychological counseling approaches, religious/spiritual orientation has become as a highly supportive element in family therapy. Spiritually-oriented applications are quite helpful when addressing problems dealt with by individuals and families. In the current study, spiritually-oriented cognitive-behavioral family therapy is addressed in light of the relevant literature. We first present a general overview of cognitive-behavioral therapy and cognitive-behavioral family therapy, after which we frame the assessment steps followed in spiritually-oriented cognitive-behavioral family therapy within a paradigm based on religion and spirituality. After that, we reveal the religious/spiritual-based cognitive-behavioral applications that may be used during family therapy. We then discuss several exercises and applications employed during spiritually-oriented cognitive-behavioral family therapy. Finally, this study seeks to fill in gaps in the relevant literature on this topic in Turkey and offer a novel perspective to practitioners and researchers.